Enraizamento de estacas de Coffea arabica L. em sistema hidropônico - Pinto, Francisco Andrés Pérez (2017)
Due to the existence of differentiated technologies and large number of raw materials in terms of seedling production, it is necessary to associate them to achieve success in this process.In the rooting cuttings and hydroponics are alternatives that can bring important contributions to the coffee propagation. The objective in this work was to study the feasibility of using different substrates in the seedlings production by rooting cuttings in a hydroponic system with different sources of minerals and different managements. A completely randomized block design was used in a subdivided plot. The experiment was conducted in a greenhouse at the Ornamental Plants - Agriculture Department of UFLA - counting on three management in hydroponic conduction (Water + Osmocote; Water + Solution; Nutritive Solution) and two types of substrate (Vermiculite and Vermiculite (70%) + Charred rice husk (30%)).The following characteristics were evaluated: survival percentage, dry weight of shoot, and root system, leaf area, chlorophyll indexand root systemcharacteristics. The nutrient solution is initially harmful to the cuttings. The initial supply of water and subsequent use of solution may be beneficial, but there is a need to work on a specific solution for coffee plants. Vermiculite was the substrate that favored the results. The mixture vermiculite + charred rice husk did not present positive results for this type of conduction. In order to obtain coffee seedlings via rooting cuttings, with greater growth and development, it is necessary to use tubes filled with vermiculite and addition of slow release fertilizer, in a hydroponic system with water and without nutrients.